Electronic structure of 3d[M(H2O)6](3+) ions from Sc(III) to Fe(III): a quantum mechanical study based on DFT computations and natural bond orbital analyses - Kallies, B; Meier, R (Inorganic chemistry, 2001)
The metal-donor atom bonding along the series of 3d[M(H2O)6](3+) ions from Sc(3+) to Fe(3+) has been investigated by density-functional calculations combined with natural localized bond orbital analyses. The M-OH(2) bonds were considered as donor-acceptor bonds, and the contributions coming from the metal ion's 3d sigma-, 3d pi-, and 4s sigma-interactions were treated individually. In this way, the total amount of charge transferred from the water oxygen-donor atoms toward the appropriate metal orbitals could be analyzed in a straightforward manner. One result obtained along these lines is that the overall extent of ligand-to-metal charge transfer shows a strong correlation to the hydration enthalpies of the aqua metal ions. If the contributions to the total ligand-to-metal ion charge transfer are divided into sigma- and pi-contributions, it turns out that Cr(3+) is the best sigma-acceptor, but its pi-accepting abilities are the weakest along the series. Fe(3+) is found to be the best pi-acceptor among the 3d hexaaqua ions studied. Its aptitude to accept sigma-electron density is the second weakest along the series and only slightly higher than that of Sc(3+) (the least sigma-acceptor of all ions) because of the larger involvement of the Fe(3+) 4s orbital in sigma-bonding. The strengths of the three types of bonding interactions have been correlated with the electron affinities of the different metal orbitals. Deviations from the regular trends of electron affinities along the series were found for those [M(H2O)6](3+) ions that are subject to Jahn-Teller distortions. In these cases (d(1) = [Ti(H2O)6](3+), d(2) = [V(H2O)6](3+), and d(4) = [Mn(H2O)6](3+)), ligand-to-metal charge transfer is prevented to go into those metal orbitals that contain unpaired d electrons. A lowering of the complex symmetry is observed and coupled with the following variations: The Ti(3+)- and V(3+)-hexaaqua ions switch from T(h)() to C(i)() symmetry while the Mn(3+)-hexaaqua ion moves to D(2)(h)() symmetry. The loss of orbital overlap leading to a diminished ligand-to-metal charge transfer toward the single occupied metal orbitals is compensated by amplified bonding interactions of the ligand orbitals with the unoccupied metal orbitals to some extent.